A Conceptual Framework for the Analysis of First-Person Shooter Audio and its Potential Use for Game Engines. (22nd January 2008) - Grimshaw, Mark; Schott, Gareth
Abstract : We introduce and describe a new conceptual framework for the design and analysis of audio for immersive first-person shooter games, and discuss its potential implications for the development of the audio component of game engines. The framework was created in order to illustrate and acknowledge the direct role of in-game audio in shaping player-player interactions and in creating a sense of immersion in the game world. Furthermore, it is argued that the relationship between player and sound is best conceptualized theoretically as an acoustic ecology. Current game engines are capable of game world spatiality through acoustic shading, but the ideas presented here provide a framework to explore other immersive possibilities for game audio through real-time synthesis.